Aspiraciones intrínsecas/extrínsecas, orientación futura y compromiso de carrera en escolares de secundaria en Lima Metropolitana - Ramos Panduro, Clara Elvira (2024)
The objective of this study is to examine the extent to which intrinsic and extrinsic aspirations predict career commitment (certainty and identification) while exploring how this relationship is mediated by future orientation (career and family domains); among Junior and Senior year high school students. The sample comprised 203 students, with 76.4% identifying as male and 23.6% as female, from private and parochial schools in Metropolitan Lima. The instruments employed demonstrated satisfactory psychometric properties. The proposed mediation model did not exhibit indicators of optimal fit. Consequently, a regression analysis was conducted that accounted for the subcomponents of the future orientation model. In the career domain, both commitment to future orientation and extrinsic aspirations were found to predict certainty in career commitment. Within the family domain, the predictors of career commitment included exploration and both types of aspirations (intrinsic and extrinsic). Female students exhibited higher levels of extrinsic aspirations, elevated levels of fear, and greater exploration of future orientation within the career domain. Conversely, male students demonstrated higher levels of fear in the family domain but placed significant value on family formation. Senior high school students displayed increased levels of fear, commitment, and exploration in the career domain. In the family domain, both hopes and identification with career commitment were notably higher. Students who had already selected a career showed elevated levels of commitment, exploration, certainty, and identification with their career commitment. The findings may offer valuable guidelines for adolescent counselors regarding the nature of aspirations, future orientation, and career commitment.